Favourableness and connectivity of a Western Iberian landscape for the reintroduction of the iconic Iberian ibex Capra pyrenaica. Issue 4 (5th October 2016) - Torres, Rita T.; Carvalho, João; Serrano, Emmanuel; Helmer, Wouter; Acevedo, Pelayo; Fonseca, Carlos
Abstract: Traditional land use practices declined throughout many of Europe's rural landscapes during the 20th century. Rewilding (i.e. restoring ecosystem functioning with minimal human intervention) is being pursued in many areas, and restocking or reintroduction of key species is often part of the rewilding strategy. Such programmes require ecological information about the target areas but this is not always available. Using the example of the Iberian ibex Capra pyrenaica within the Rewilding Europe framework we address the following questions: (1) Are there areas in Western Iberia that are environmentally favourable for reintroduction of the species? (2) If so, are these areas well connected with each other? (3) Which of these areas favour the establishment and expansion of a viable population of Iberian ibex in a reintroduction programme? We modelled environmental favourableness for the species in the Iberian Peninsula using a logistic regression with a forward–backward stepwise procedure, and assessed landscape connectivity using a graph analytical approach after downscaling the model to the Western Iberia region. Our results indicate that several habitat patches in the study area present favourable environmental conditions for reintroduction of the Iberian ibex. Overall, most of the habitat connectivity was concentrated in northern and central patches. We highlight the potential and practical application of the analytical protocol used, for successful integration of species distribution modelling and landscape connectivity in the design of broad-scale reintroduction and recovery programmes.